Arbuscular mycorrhizal fungi increased peanut (Arachis hypogaea L.) yield by changing the rhizosphere microbial community structure in saline-alkali soil - Kang, Jia; Yang, Wenlong; Liu, Shangwu; Xuan, Ning; Shao, Yahui; Geng, Yun; Afzal, Muhammad; Zhang, Yingxin; Yue, Shousong; Mushtaq, Rubina; Chen, Gao (Frontiers in Microbiology, 2023)
Arbuscular mycorrhizal fungi (AMF) have demonstrated the potential to enhance the saline-alkali tolerance in plants. Nevertheless, the extent to which AMF can ameliorate the tolerance of salt-sensitive plants to alkaline conditions necessitates further investigation. The current study is primarily centered on elucidating the impact of AMF on the growth of the Huayu22 (H22) when cultivated in saline-alkaline soil. We leveraged DNA of rhizosphere microorganisms extracted from saline-alkali soil subjected to AMF treatment and conducted high-throughput sequencing encompassing 16S rRNA gene and ITS sequencing. Our findings from high-throughput sequencing unveiled Proteobacteria and Bacillus as the prevailing phylum and genus within the bacterial population, respectively. Likewise, the predominant fungal phylum and genus were identified as Ascomycota and Haematonectria. It is noteworthy that the relative abundance of Proteobacteria, Actinobacteria, Chloroflexi, Bacteroidetes, and Ascomycota exhibited significant increments subsequent to AMF inoculation. Our investigation into soil enzyme activity revealed a remarkable surge post-AMF inoculation. Notably, the amounts of pathogen growth inhibitory enzymes and organic carbon degrading enzymes rise, as predicted by the putative roles of microbial communities. In saline-alkali soil, inoculation of AMF did boost the yield of H22. Notable improvements were observed in the weight of both 100 fruits and 100 grains, which increased by 20.02% and 22.30%, respectively. Conclusively, this study not only provides a theoretical framework but also furnishes empirical evidence supporting the utilization of AMF as a viable strategy for augmenting the yield of salt-sensitive plants grown in alkaline conditions.